Course of Sexual Dysfunction in Different Domains among Hypertensive Patients: A Longitudinal Study in a Tier 2 City in India - Ankit Halder; Navna Panchami Ravindran; Devavrat Harshe; Sneha Harshe; Gurudas Harshe; Avinanda Biswas; Dhakshana Pushpanathan; Abhishek Shewale; Sucharita Patra; Aditya Nair (Indian Journal of Private Psychiatry)
Introduction: A greater risk of sexual dysfunction (SDys) is found in hypertensive individuals. The study aimed to chronicle the course of dysfunction in different domains of male and female sexual function in patients of essential hypertension and correlate the findings with different patient characteristics. Materials and methods: The study was conducted in a semi-urban outpatient department setting, in Kolhapur city, consisting of 360 patients of essential hypertension on antihypertensive therapy for at least 2 years fulfilling the criteria of the study protocol in General medicine OPD of DY Patil Hospital and Research Institute. Detailed clinical history, examination, and laboratory investigations were carried out. Clinical data were collected using standard questionnaires. Demographics and clinical data were analyzed in R-studio software (v.1.2.5001). Result: Of the 180 males, 46.11% (n = 83), and of 180 females, 38.89% (n = 70) had dysfunction in at least one domain. Among the 83 males with dysfunction, erectile dysfunction (Edys) was the commonest (100%) and lack of intercourse satisfaction (49%) was the least. Among the 70 females with dysfunction, lack of sexual desire was the commonest (78%) and lack of lubrication (46%) was the least. Age, antihypertensive drug type, and duration of antihypertensive treatment were significantly associated with dysfunction (p <0.005). Sexual dysfunction improved in all the 25 males and 23 females who took treatment for it in the form of drugs and psychotherapy. Conclusion: Sexual dysfunctions are more prevalent in hypertensive individuals. It should be aggressively screened, avoided, and treated since it is a sign of increased cardiovascular risk that also reduces the quality of life.